Socioeconomic profile of children who did not join the rotavirus vaccine schedule - Martins, Gabriella Miranda (2011)
Introduction: Rotavirus has a universal distribution, causing episodes of acute gastroenteritis, endemic in tropical regions. Immunization is the most effective way to avoid it. Children from an environment with better conditions and higher socioeconomic factors have better prognosis, while those coming from poor families have more risk of disease severity. Objective: To evaluate the socioeconomic profile of children’s families that did not join the rotavirus vaccine schedule. Methods: Through the shade card, used by community health agents of the Cecy Fortes Health Center, the vaccination status of children born from April 2009 to January 2011 was analyzed. The family files of children who did not join the rotavirus vaccine schedule were evaluated, based on the data on these files, about their socioeconomic profile. Results and discussion: From the 183 cards shadow included in the study, 25 were incomplete or missing the vaccine schedule and had their family files evaluated. Sixty-eight percent of these families have incomes below two minimum wages, which represents risk of gravity of the diarrheal diseases. However, 96% of the parents are illiterate, and 100% of families live in houses with adequate conditions of sanitation, which infer a good prognosis. Conclusion: The children’s families are largely composed of literate parents, have family income below two minimum wages, and satisfactory conditions of housing and sanitation.